Claude Vivier and Karlheinz Stockhausen : moments from a double portrait / Claude Vivier and Karlheinz Stockhausen: moments from a double portrait - Gilmore, Bob (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractThat Karlheinz Stockhausen played a crucial role in the musical development of the young Claude Vivier is beyond question. In an autobiographical note written in 1975, Vivier noted: “Born in Montreal in 1948. Born to music with Gilles Tremblay in 1968. Born to composition with Stockhausen in 1972. Indeed, the widespread view is that, during the years he studied formally with Stockhausen at the Hochschule für Musik in Cologne (1972-74), Vivier hero-worshipped the German composer. Widely regarded as one of the leading figures of the international musical avant-garde, Stockhausen had held for two decades a position that, by the time Vivier began formal studies with him, was under assault. The whole system of values for which he stood, musical and otherwise, was being questioned to its foundations, even, in some quarters, reviled and demonised. The relationship between the young Vivier and his distinguished teacher is therefore a complex one. While Vivier evidently fell powerfully under the sway of Stockhausen’s music and ideas and his charismatic and domineering personality, this article explores the effect on him of the changing attitudes toward Stockhausen as the 1970s wore on. This article attempts to paint the complex relationship between the two men, focusing on the years of their closest contact – 1971-1974 – a time when both they and the world around them were undergoing profound transformation.